Detectable troponin below the 99th percentile predicts survival in patients with cardiovascular disease. (14th October 2021) - Michel, L; Hendricks, S; Dykun, I; Rassaf, T; Mahabadi, A A; Totzeck, M
Abstract: Background: Patients with cardiovascular disease and elevated troponin above the 99th percentile of the upper reference limit are at increased risk for major adverse events, and usually require urgent treatment, including coronary angiography. Meanwhile, patients with detectable troponin levels below the 99th percentile represent a more heterogeneous collective at need for further risk stratification. Purpose: This study aims to determine the prognostic implications of detectable troponin below the 99th percentile of the upper reference limit compared to troponin lower than the detectable range in patients with cardiovascular disease. Methods: The ECAD registry was screened for patients without detectable troponin and with detectable troponin below the 99th percentile upon admission. Patients with ST-segment elevation myocardial infarction and patients with admission troponin above the 99th percentile were excluded. Troponin was determined by Siemens Dimension Troponin I (detectable limit: 40 ng/L, 99th percentile: 70 ng/L) and contemporary Centaur high-sensitive Troponin I Ultra (detectable limit: 6 ng/L, 99th percentile: 40 ng/L) assays. Overall survival was defined as the primary endpoint. Cox regression analysis was used to determine the association of troponin groups with incident mortality, adjusting for age, sex, systolic blood pressure, low-density lipoprotein (LDL) cholesterol, smoking status, and family history of premature cardiovascular disease. Results: 14, 776 consecutive patients (mean age was 65.35±12.74 years, with 71.3% male) with hospital admissions between 2004 and 2019 were included to the analysis. 11, 965 patients had troponin levels below the detectable limits, while 2, 811 patients had detectable troponin below the 99th percentile. During a mean follow-up of 4.25±3.76 years, 2379 (16.1%) deaths of any cause occurred. The overall mortality was higher in patients with detectable troponin below the 99th percentile compared to patients without detectable troponin (20.8% vs. 15.0%, p<0.001). In multivariable regression analysis, detectable troponin below the 99th percentile was significantly associated with all-cause mortality (HR 1.71; 95% CI 1.46–2.01; p<0.001). At 30 months, there was a significant stepwise relationship with increasing overall mortality between the tertiles of troponin levels (tertile 1, HR 1.62 (1.39–1.90); tertile 2, HR 1.88 (1.63–2.16); tertile 3, HR 2.02 (1.74–2.35)). Conclusions: Detectable troponin below the 99th percentile is an independent predictor of overall mortality in patients with cardiovascular disease, and shows a gradually higher risk with increasing troponin levels. Every finding of detectable troponin in patients with cardiovascular disease should therefore prompt further diagnostic work-up. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): UMEA Young Clinical Scientist Grant, Medical faculty, University Duisburg-Essen (Hendricks)